Pengaruh metode ummi dalam meningkatkan kemampuan membaca Al-Quran pada siswa di MI Attaqwa 05 Kabupaten Bekasi - Maulana, Ahmad Fawzy; Fatimah, Titim; Rohmah, Siti Khazanatu (Latifah Pres, 2024)
This study aims to determine the difference in the average results of the ability to read the Quran fifth grade students in the subjects of Al-Quran Hadith, this study uses quasi-experimental design with non-equivalent control group design. The population of this study was all fifth grade students of one of the MI in Bekasi regency for the 2023/2024 academic year. The study population was 15 experimental class students and 15 Control class students. Data collection through the ability to read the Quran. The test instruments in this study were developed by applying expert judgment. Data analyzed by T test showed that the value of t = 10.089 and the value of GIS. (2 - tailed) = 0.00 < 0.05 then Ho is rejected. This means that there is a difference in the average increase in the results of the ability to read Al-Quran fifth grade students in the subjects of Al-Quran Hadith using the method of UMMI with Iqra method. The average value of N-Gain control class is 0.28 with low criteria. While the experimental class is equal to 0.36 with medium criteria. So it can be concluded that this study using the results of the ability to read the Quran UMMI method is one alternative to make it easier for students to improve the results of reading the Quran.